Potential Role of Epstein Barr Virus in Oral Squamous Cell Carcinoma Development - Sara kareem Shalal (American Journal of Biology and Natural Sciences, 2025)
Background: Epstein Barr virus is one of the most commonly affective oncogenic viruses that may cause several types of cancer such as oral cancer. Aim of the study: This study aims to assess the role of EBV in making a progression in OSCC and its deterioration to cases with OSCC. Novelty: This is the first study on patients with OSCC was conducted in Iraq and trying to find the correlation between EBV and OSCC incidence and exaggeration. Methods: A case control study was conducted on 70 cases with OSCC and 70 subjects as controls for 8 months of investigation and follow up at Musol hospital in Iraq. Results: Among 70 cases were diagnosed with OSCC and 70 were considered as controls and mean age among cases and controls was 41.57±7.4 and 40.7±6.2, respectively. The risk factors reported were distributed as smoking which was more among controls than cases while alcoholism and betel quid chewing was higher among cases (n=7 and 1). The site of tumor among OSCC cases was reported as the tumors in buccal mucosa were the most predominant (n=26, 37.14%). The most cases are EBV positive (n=41). The association between risk factors and prevalence of EBV among cases showed that all risk factors are significantly associated with incidence of EBV (p < 0.001) and the site of tumor reported that all sites except for palate were significantly associated with prevalence of EBV (p < 0.05). Conclusion: EBV is readily and significantly correlated with development and prediction of OSCCs among different cases.